Coordination chemistry of pnictogenylboranes towards group 6 transition metal Lewis acids. Issue 4 (6th September 2022) - Lehnfeld, Felix; Hegen, Oliver; Balázs, Gábor; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: The coordination behavior of different pnictogenylboranes towards group 6 metal Lewis acids is investigated. The resulting complexes with phosphanylboranes [(CO)4 M(PH2 BH2  ⋅ NMe3 )2 ] (M=Cr, Mo, W; 1–3 ), arsanylboranes ([(CO)4 M(AsH2 BH2  ⋅ NMe3 )2 ] (M=Cr, Mo, W; 4 –6 ) and t Bu‐substituted phosphanylboranes [(CO)4 M( t BuPHBH2  ⋅ NMe3 )2 ] (M=Cr, W; 7–8 ) are fully characterized by multinuclear NMR spectroscopy, single crystal X‐ray diffraction and IR spectroscopy. The systematic nature of the approach of the synthesis and the high purity of the compounds enable a comparative investigation of the coordination behavior of pnictogenylboranes. The influences of the metal center, the pnictogen atom and the substituent at the pnictogen atom on the coordination behavior of pnictogenylboranes are compared. Abstract :